1996
DOI: 10.1116/1.589006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization by x-ray photoelectron spectroscopy of the chemical structure of semi-insulating polycrystalline silicon thin films

Abstract: The x-ray photoelectron spectroscopy (XPS) technique has been used to investigate the composition of semi-insulating polycrystalline silicon (SIPOS) films having oxygen contents of 10 and 35 at. % prepared by low pressure chemical vapor deposition. XPS analysis has demonstrated that the film compositions can be qualitatively described by means of the five Si-SixO4−x tetrahedra (with 0≤x≤4 and integer) predicted by the statistical random bonding model (RBM). However, the quantitative analysis of the XPS spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 24 publications
(37 reference statements)
1
21
0
Order By: Relevance
“…21 It is also reported that thermal annealing converts a partially oxidized SiϪSi n O 4Ϫn (nϽ4) tetrahedral structure to SiϪO 4 tetrahedral structure, confirmed by x-ray photoelectron spectroscopy. 22 On the other hand, there remain silicon rich phases (SiϪSi n O 4Ϫn ) after the thermal annealing at 1000°C.…”
Section: Discussionmentioning
confidence: 99%
“…21 It is also reported that thermal annealing converts a partially oxidized SiϪSi n O 4Ϫn (nϽ4) tetrahedral structure to SiϪO 4 tetrahedral structure, confirmed by x-ray photoelectron spectroscopy. 22 On the other hand, there remain silicon rich phases (SiϪSi n O 4Ϫn ) after the thermal annealing at 1000°C.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, such suboxide structures can persist even at 1000°C. 13 We suggest that the GBs are a mixture of Si-O 4 and silicon-rich structures, the former with an energy gap close to silicon dioxide and the latter with a lower energy gap. These energy gaps and the local trapped charge create potential barriers at the GBs, and a mix of these structures leads to a local distribution in V B .…”
Section: Figmentioning
confidence: 99%
“…This has been observed in silicon suboxide, where the silicon-rich bonding structure Si-Si 4Ϫn O n (nϽ4) forms the major portion of the suboxide. High-temperature annealing can convert some parts of this to a Si-O 4 tetrahedral structure 13 or cause phase separation into nanocrystalline silicon and silicon dioxide. 14 In our films, the GB volume may be limited for nanocrystalline silicon formation, and a Si-O 4 structure may form locally.…”
Section: Figmentioning
confidence: 99%
“…The peak located at 103.8 eV is the signature peak for Si bonded to four O atoms (SiO 2 ) whereas the peak located at 99.3 eV corresponds to a Si atom tetrahedrally bonded to four Si atoms. 22 Because the nanocrystal layer is separated from the substrate by 25 nm thick SiO 2 , the entire signal at 99.3 eV originates from Si in the nanocrystals and the contribution from the c-Si substrate is negligible. With increasing oxidation duration, the peak at 99.3 eV reduces and the peak at 103.8 eV increases indicating consumption of Si in the nanocrystal layer and formation of SiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The SiO 2 formed during the oxidation process is stoichiometric since no shoulders or peaks ͑in the region between 100 and 103 eV͒ attributable to the presence of SiO x (xϽ2) suboxides are observed. 22 Figure 7͑a͒ shows the ⌬͑͒ image recorded prior to charging the 30 min oxidized nanocrystal layer. The ⌬͑͒ image obtained 12 min after charging the nanocrystals is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%